An international multicenter cohort atudy on β-blockers for the treatment of symptomatic children with catecholaminergic polymorphic ventricular tachycardia - Peltenburg, Puck J.; Kallas, Dania; Bos, Johan M.; Lieve, Krystien V.V.; Franciosi, Sonia; Roston, Thomas M.; Denjoy, Isabelle; Sorensen, Katrina B.; Ohno, Seiko; Roses-Noguer, Ferran; Aiba, Takeshi; Maltret, Alice; et al. (Circulation, 2022)
Background: - - Symptomatic children with catecholaminergic polymorphic ventricular tachycardia (CPVT) are at risk for recurrent arrhythmic events. β-Blockers decrease this risk, but studies comparing individual β-blockers in sizeable cohorts are lacking. We aimed to assess the association between risk for arrhythmic events and type of β-blocker in a large cohort of symptomatic children with CPVT. - - Methods: - - From 2 international registries of patients with CPVT, RYR2 variant-carrying symptomatic children (defined as syncope or sudden cardiac arrest before β-blocker initiation and age at start of β-blocker therapy <18 years), treated with a β-blocker were included. Cox regression analyses with time-dependent covariates for β-blockers and potential confounders were used to assess the hazard ratio (HR). The primary outcome was the first occurrence of sudden cardiac death, sudden cardiac arrest, appropriate implantable cardioverter-defibrillator shock, or syncope. The secondary outcome was the first occurrence of any of the primary outcomes except syncope. - - Results: - - We included 329 patients (median age at diagnosis, 12 [interquartile range, 7-15] years, 35% females). Ninety-nine (30.1%) patients experienced the primary outcome and 74 (22.5%) experienced the secondary outcome during a median follow-up of 6.7 (interquartile range, 2.8-12.5) years. Two-hundred sixteen patients (66.0%) used a nonselective β-blocker (predominantly nadolol [n=140] or propranolol [n=70]) and 111 (33.7%) used a β1-selective β-blocker (predominantly atenolol [n=51], metoprolol [n=33], or bisoprolol [n=19]) as initial β-blocker. Baseline characteristics did not differ. The HRs for both the primary and secondary outcomes were higher for β1-selective compared with nonselective β-blockers (HR, 2.04 [95% CI, 1.31-3.17]; and HR, 1.99 [95% CI, 1.20-3.30], respectively). When assessed separately, the HR for the primary outcome was higher for atenolol (HR, 2.68 [95% CI, 1.44-4.99]), bisoprolol (HR, 3.24 [95% CI, 1.47-7.18]), and metoprolol (HR, 2.18 [95% CI, 1.08-4.40]) compared with nadolol, but did not differ from propranolol. The HR of the secondary outcome was only higher in atenolol compared with nadolol (HR, 2.68 [95% CI, 1.30-5.55]). - - Conclusions: - - β1-selective β-blockers were associated with a significantly higher risk for arrhythmic events in symptomatic children with CPVT compared with nonselective β-blockers, specifically nadolol. Nadolol, or propranolol if nadolol is unavailable, should be the preferred β-blocker for treating symptomatic children with CPVT.
Im Titel ist "beta" als griechischer Buchstabe dargestellt
Ursprünglich veröffentlicht: 7. Dezember 2021
Gesehen am 14.05.2024